Keanekaragaman Hayati Vegetasi pada Sistem Agroforest di Desa Sungai Sekonyer, Kabupaten Kotawaringin Barat, Kalimantan Tengah - Adisti Permatasari Putri Hartoyo; Nurheni Wijayanto; Esperansa Olivita; Hanifa Rahmah; Amelia Nurlatifah (Jurnal Silvikultur Tropika, 2019)
Sungai Sekonyer village is a village that bordered by Tanjung Puting National Park (TNTP). Agroforest system is one of the land uses that considering ecology, socio-economy aspects in supporting buffer zone TNTP. The objectives of this research were to analyze the structure and composition of agroforest system, as well as to analyze biodiversity vegetation of the agroforestry system in Sungai Sekonyer Village, West Kotawaringin Regency, Central Kalimantan. This research used purposive sampling and vegetation analysis methods. The results showed that the dominant species at sapling level in agroforest system-1 was oil palm (Elaeis guineensis) with IVI 121.54%, while in agroforest system-2 there was no sapling. The dominant species at pole level both in agroforest systems 1 & 2 was rubber (H. brasiliensis) with IVI respectively 184.88% and 187.08%. The dominant species at tree level in agroforest system-1 was sengon (F. moluccana) with IVI=128.47%, while in agroforestry system-2 was jengkol (A. pauciflorum) with IVI=121.32%. The diversity indices (H’) and species richness indices (Dmg) for both agroforestry systems were categorized as low. Agroforest management, socio-economic aspect, ecological site, and market are the main factor for species selection that indirectly affecting biodiversity status in agroforest system. Enrichment planting using high economic value species that is suitable to the ecological site is necessary to increase community income as well as biodiversity status. Key words: agroforest, Sungai Sekonyer Village, vegetation biodiversity